Morphotypes, preservation, and taphonomy of dinosaur footprints, tail traces, and swim tracks in the largest tracksite in the world: Carreras Pampa (Upper Cretaceous), Torotoro National Park, Bolivia - Raúl Esperante; Jeremy A. McLarty; Kevin E. Nick; Lance R. Pompe; Roberto E. Biaggi; Helen D. Baltazar Medina; Nelson A. Llempen; Ángela B. Limachi Silvestri; Lourdes Lidia Mamani Quispe; Antonio Joaquín Garre Cano; Wilson Quiroga Saavedra; Germán Rocha Rodríguez (PLoS ONE, 2025)
The Carreras Pampa tracksite in the Torotoro National Park, Bolivia, records a wealth of dinosaur tracks, tail traces, and swim tracks. In this study, we report 1321 trackways and 289 solitary tracks, totaling 16,600 theropod tracks, 280 swim trackways, totaling 1,378 swim tracks, and several trackways with tail traces. Numerous avian tracks occur locally and are associated with the theropod tracks. These tracks and trackways are located within nine study sites of the same exposed tracking surface with a total area of approximately 7485 m 2 . We describe eight preservation styles and 11 morphotypes for walking tracks, and three morphotypes for swim tracks. Tracks range in size from miniature to large. The range of track sizes and the diversity of morphotypes suggest that the Carreras Pampa tracksite represents a diverse group of trackmakers. Track depths vary from very shallow to very deep both within and among trackways, suggesting that the rheological conditions of the sites changed in time and space. We present estimates of the speeds, gaits, and sizes of trackmakers and propose diverse behaviors indicated by the trackways. Notably, trackways at the Carreras Pampa tracksite indicate that a significantly higher proportion of trackmakers had relative stride lengths above 2.0 compared to other sites. The trackways show a strong, bimodal orientation, probably moving along the paleocoastline. Other forms of bioturbation and fossils were found in association with the tracks. We compare our findings at the Carreras Pampa track site to those from other sites in various locations. The quality of preservation, the exceptionally high number of tracks, and the diversity of behaviors recorded make the Carreras Pampa tracksite one of the premier dinosaur track sites in the world.